Influence of daily social stimulation on behavioral and physiological outcomes in an animal model of PTSD. Issue 5 (15th April 2016) - Seetharaman, Shyam; Fleshner, Monika; Park, Collin R.; Diamond, David M.
Abstract: Introduction: We have shown in previous work that acute episodes of predator exposure occurring in the context of chronic social instability produced PTSD‐like sequelae in rats. Our animal model of PTSD contained two components: (1) acute trauma, immobilization of rats in close proximity to a cat twice in 10 days, and (2) chronic social instability, 31 days of randomized housing of cage cohorts. Here we tested the hypothesis that daily social stimulation would block the development of the PTSD‐like sequelae. Methods: Beginning 24 h after the first cat exposure, adult male rats were given our established PTSD model, alone or in conjunction with daily social stimulation, in which all rats within a group interacted in a large apparatus for 2 h each day for the final 30 days of the PTSD regimen. All behavioral, for example, anxiety, memory, startle testing, and physiological assessments, for example, body growth, organ weights, and corticosterone levels, took place following completion of the psychosocial stress period. Results: Daily social stimulation blocked the expression of a subset of PTSD‐like effects, including predator‐based cued fear conditioning, enhanced startle response, heightened anxiety on the elevated plus maze and the stress‐induced suppression of growth rate. We also found that social stimulation and psychosocial stress produced equivalent outcomes in some measures, including adrenal and heart hypertrophy, thymus atrophy, and a reduction in poststress corticosterone levels. Conclusions: Daily exposure of rats to a highly social environment blocked the development of a subset of trauma‐induced sequelae, particularly fear‐related outcomes. It is notable that daily social stimulation normalized a subset, but not all, of the PTSD‐like effects. We discuss our findings in the context of the literature demonstrating that social stimulation can counteract the adverse effects of traumatic stress on behavioral and physiological measures, as well as to produce its own stress‐like outcomes. Abstract : We have a well‐established rat model of PTSD based on predator exposure occurring on a background of social instability. In this work, we have shown that daily social stimulation blocked the expression of predator‐based cued fear conditioning, normalized the startle response, prevented heightened anxiety on the elevated plus maze, and reversed the stress‐induced suppression of growth rate. These findings provide additional validation of our animal PTSD model by demonstrating that, as in clinical PTSD, the social environment is a critical factor in modulating one's response to trauma.